The Influence of Audit Risk, Professional Sketicism, Independence, and Auditor Professionalism on Fraud Detection (Emiris Study at BPKP Representative Office, Jambi Province) - Shinta Adelia Sari; Enggar Diah Puspa Arum; Fredy Olimsar (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of this study was to empirically determine the effect of audit risk, professional skepticism, independence, and auditor professionalism on fraud detection at the Representative Office of the Financial and Development Supervisory Agency, Jambi Province. This study involved all auditors at the Jambi Province BPKP Representative Office with a total of 72 people as a population. The sample is determined using the total sampling method. The total sampling method was used to determine the sample. Data collection was collected through the questionnaire method and SmartPLS version 3.0 software was used to analyze the data. Research results show that audit risk has no effect on fraud detection; Professional skepticism affects detection; and Auditor independence has no effect on fraud detection; and the professionalism of the auditor influences the detection of fraud